Analysis on E-Commerce Marketing Channel Based on Age Segmentation: A Case Study of Fabelio - Tamariksa, Maria Imelda; Iskandar, Budi Permadi (Journal of Business and Management, 2017)
Abstract.Background: E-commerce is business transactions process through the network, including online advertising, ordering, payment and the corresponding goods distribution and customer service. As one of the core e-commerce business activities, internet marketing strategy should be formulated carefully since it contributes to the firm’s performance as well. By analyzing the current performance of their promotion channels, the researcher aims to point out which channel suits best to certain age segment.Methods: Previous literature has concluded that demographic do play significant role in internet browsing behavior. However, the influence only occurred through age segment, while gender segment does not play an important role. Using Google Analytics, the researcher would like to find the preferable promotion channel based on the age segmentation.Results: It is showed that for age segment 18 to 44 years old, they prefer to reach the website through search query which result includes the ads of Fabelio website. Meanwhile, for 45 years old and above, they were attracted to visit Fabelio through ads which are place in a popular social network, Facebook.Conclusion: Different age segments visit Fabelio site through different channel, depending on their internet-browsing behavior. Therefore, marketing strategy has to suit the target market from certain age segments. Keywords: Age Segmentation, E-commerce, Promotion Channel, Web Analytics, Web Metrics.